Pengaruh Suku Bunga, Inflasi dan Kurs Terhadap Harga Saham Sub Sektor Logam dan Sejenisnya yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2009-2018 - Lia Sari; Zein Ghozali; Hilwa Anggraini; Roy Saleh; Nelly (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
The purpose of this study was to determine the effect of interest rates, inflation, and exchange rates on stock prices for the precious metals sub-sector and the like listed on the Indonesian Stock Exchange for the period 2009 - 2018. This research uses a quantitativedescriptive approach. The data analysis technique uses multiple regression analysis with the help of the SPSS 24.00 program. Hypothesis testing uses the t test (partial test) and F test (simultaneously). This study aims to find the relationship between the independent variables, namely interest rates (X1), inflation (X2) and exchange rates (X3) with the dependent variable,namely stock prices (Y). The sample used in this study is with an error rate of 5%, namely by using a sample of 14 (fourteen) companies in the metal and similar sub-sectors on the Indonesia Stock Exchange (IDX) for the period 2009 - 2018. The results of this study indicate that the independent variable interest rate (X1) has a significant positive impact on stock prices in the Metals and the Like Subsector. While the inflation variables (X2 and Exchange Rate (X3) have a significant negative impact on the share prices of the Metals and the Like Subsector on the Indonesia Stock Exchange for the period 2009 - 2018. Interest Rates, Inflation and Exchange rates as a whole have a significant influence on stock prices. The independent variables in the form of Interest Rates, Inflation, and Exchange Rates are only able to influence stock prices in the basic and chemical industrial sectors by 12%, the remaining 88% is the influence of other causes or factors not examined.